Synchronization of Fractional Order Uncertain BAM Competitive Neural Networks - M. Syed Ali; M. Hymavathi; Syeda Asma Kauser; Grienggrai Rajchakit; Porpattama Hammachukiattikul; Nattakan Boonsatit (Fractal and Fractional, 2021)
This article examines the drive-response synchronization of a class of fractional order uncertain BAM (Bidirectional Associative Memory) competitive neural networks. By using the differential inclusions theory, and constructing a proper Lyapunov-Krasovskii functional, novel sufficient conditions are obtained to achieve global asymptotic stability of fractional order uncertain BAM competitive neural networks. This novel approach is based on the linear matrix inequality (LMI) technique and the derived conditions are easy to verify via the LMI toolbox. Moreover, numerical examples are presented to show the feasibility and effectiveness of the theoretical results.